Find an equation for the nth term of the sequence.

-1, -4, -16, -64, ...

an = -1 • 4n - 1
an = -1 • 4n
an = 4 • -1n
an = 4 • -1n + 1

Respuesta :

Step-by-step explanation:

Step 1:  Find the sequence

Option A

[tex]a(-1) = -1*4(-1)-1[/tex]

[tex]a(-1) = -1 * -4 - 1[/tex]

[tex]a(-1) = 4 - 1[/tex]

[tex]a(-1) = 3[/tex]

Option B

[tex]a(-1) = -1 * 4(-1)[/tex]

[tex]a(-1) = -1 * -4[/tex]

[tex]a(-1) = 4[/tex]

Option C

[tex]a(-1) = 4 * -1(-1)[/tex]

[tex]a(-1) = 4 * 1[/tex]

[tex]a(-1) = 4[/tex]

Option E

[tex]a(-1) = 4 * -1(-1) + 1[/tex]

[tex]a(-1) = 4 * 1 + 1[/tex]

[tex]a(-1) = 4 + 1[/tex]

[tex]a(-1) = 5[/tex]

Answer:  For some reason, none of the answer choices match

Answer:

First one

Step-by-step explanation:

It is a Geometric sequence with:

first term: -1

common ratio: -4/-1 = 4

Nth term: a × r^(n-1)

-1 × 4^(n-1)